Fibrinolytic Proteins and Factor XIII as Predictors of Thrombotic and Hemorrhagic Complications in Hospitalized COVID-19 Patients - Marchetti, Marina; Gomez-Rosas, Patricia; Russo, Laura; Gamba, Sara; Sanga, Eleonora; Verzeroli, Cristina; Ambaglio, Chiara; Schieppati, Francesca; Restuccia, Francesco; Bonanomi, Ezio; Rizzi, Marco; Fagiuoli, Stefano; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction In a prospective cohort of hospitalized COVID-19 patients, an extensive characterization of hemostatic alterations by both global and specific assays was performed to clarify mechanisms underlying the coagulopathy and identify predictive factors for thrombotic and hemorrhagic events during hospitalization. Material and methods Intensive care (ICU, n=46) and non-ICU (n=55) patients were enrolled, and the occurrence of thrombotic and hemorrhagic events was prospectively monitored. At study inclusion, thromboelastometry together with the measurement of specific coagulation proteins and hypercoagulation markers was performed. Results Patients (median age 67 years) showed significantly shorter clot formation time together with greater maximum clot firmness by thromboelastometry, increased levels of F1+2 and D-dimer, as biomarkers of hypercoagulability, and of procoagulant factors V, VIII, IX, XI and fibrinogen, while FXIII was significantly reduced. The concentration of fibrinolytic proteins, t-PA and PAI-1 were elevated in the overall cohort of patients. Many of these hemostatic alterations were significantly greater in ICU compared to non-ICU subjects and, furthermore, they were associated with inflammatory biomarker elevation (i.e., IL-6, CRP, neutrophil to lymphocyte ratio [NLR] and procalcitonin). After enrollment, 7 thrombosis and 14 major bleedings occurred. Analysis of clinical and biological data identified increased t-PA, PAI-1 and NLR values as independent predictive factors for thrombosis, while lower FXIII levels were associated with bleeding. Conclusions This study demonstrates alterations in all different hemostatic compartments analyzed, particularly in severe COVID-19 conditions, that strongly correlated with the inflammatory status. A potential role of fibrinolytic proteins together with NLR and of FXIII as predictors of thrombotic and hemorrhagic complications, respectively, is highlighted.